Project Discrepancies in Roadway Construction and Preservation: A Statistical Analysis of Public–Private Partnership Contract Types in the US - Nahidi, Seyedata; Fountas, Grigorios; Sarvani, Sonduru P.; Sarwar, Md Tawfiq; Anastasopoulos, Panagiotis Ch. (Frontiers in Built Environment, 2017)
At the planning stage of a roadway construction or preservation project, public agencies face a crucial challenge; to adopt and implement the appropriate contractual framework that can minimize the anticipated project discrepancies, on the basis of project-specific conditions. Focusing on Public-Private Partnerships (PPP), a deeper understanding of the factors that affect each type of discrepancy can assist public agencies in thoroughly evaluating and comparing PPP options. This paper seeks to provide an empirical but comprehensive analysis on PPP-specific project discrepancies, by identifying influential factors that significantly affect cost savings, cost overrun, change orders, and time delays in roadway projects. Using data from 645 PPP projects implemented in the USA between 1996 and 2011, seven popular PPP contracting approaches in the USA were considered in the analysis, and a number of random parameters linear and non-linear statistical models were estimated by PPP approach. The results demonstrate that PPP-specific attributes such as project cost, size, types of constituent activities, and expected duration, have mixed effects on the occurrence and the magnitude of each type of discrepancy.